Evolutionary bottlenecks in brackish water habitats drive the colonization of fresh water by stingrays. (11th July 2017) - Kirchhoff, K. N.; Hauffe, T.; Stelbrink, B.; Albrecht, C.; Wilke, T.
Abstract: Species richness in freshwater bony fishes depends on two main processes: the transition into and the diversification within freshwater habitats. In contrast to bony fishes, only few cartilaginous fishes, mostly stingrays (Myliobatoidei), were able to colonize fresh water. Respective transition processes have been mainly assessed from a physiological and morphological perspective, indicating that the freshwater lifestyle is strongly limited by the ability to perform osmoregulatory adaptations. However, the transition history and the effect of physiological constraints on the diversification in stingrays remain poorly understood. Herein, we estimated the geographic pathways of freshwater colonization and inferred the mode of habitat transitions. Further, we assessed habitat‐related speciation rates in a time‐calibrated phylogenetic framework to understand factors driving the transition of stingrays into and the diversification within fresh water. Using South American and Southeast Asian freshwater taxa as model organisms, we found one independent freshwater colonization event by stingrays in South America and at least three in Southeast Asia. We revealed that vicariant processes most likely caused freshwater transition during the time of major marine incursions. The habitat transition rates indicate that brackish water species switch preferably back into marine than forth into freshwater habitats. Moreover, our results showed significantly lower diversification rates in brackish water lineages, whereas freshwater and marine lineages exhibit similar rates. Thus, brackish water habitats may have functioned as evolutionary bottlenecks for the colonization of fresh water by stingrays, probably because of the higher variability of environmental conditions in brackish water.